A preliminary epidemiological study of pinworm infection in Thaklong Municipal Early Childhood Development Center and Rangsit Babies’ Home, Pathum Thani, Thailand - Taylor, A; Saichua, P; Rhongbutsri, P; Tiengtip, R; Kitvatanachai, S; Taylor, W (BioMed Central, 2018)
Objectives: We investigated the prevalence and risk factors for Enterobius vermicularis in children at the Thaklong Municipal Early Childhood Development Center (TMECDC), and the Rangsit Babies’ Home (RBH) in Pathum Thani, Thailand using the Scotch tape method. Results: 397 children aged 3–6 years were sampled (male = 198); 31 (7.8%) were E. vermicularis positive: 1 (TMECDC) and 30 (RBH). 264/397 (66.50%) of parents had incomes > 12,000 baht/month and 313/397 (78.84%) were educated from primary school to college. Univariate analysis identified (i) age 5–6 years, (ii) female sex, (iii) lower education of mother/father, (iv) being a house wife, (v) being a low income family, (vi) being resident in the orphanage, (vii) reporting anorexia and/or fever, and (viii) not washing their bottoms as factors for a positive slide. By logistic regression, education level and age group were independently associated with a positive Scotch tape result. Older children and higher family education had opposing associations with E. vermicularis. Strategies to control pinworm infection should focus on high-risk children in orphanages.